Akulturasi Nilai-Nilai Kearifan Lokal Mengawe Dalam Agama Buddha - Joni Pranata Pranata; Hadion Wijoyo; Julia Surya (STAB Maitreyawira, 2021)
ABSTRACTCultural customs develop in the middle of society with their respective characteristics, acculturated with their beliefs. The cultural traditions that are integrated with Buddhism are complementary and in line with each area where Buddhism develops, this makes Buddhist communities have their own characteristics in each region. The purpose of writing the article Acculturation of the Local Wisdom Values of Mengawe in Buddhism will be able to provide understanding and understanding of the local values that exist in Buddhist society that have been integrated into the tradition so that Buddhists in each region have an understanding of the diversity of traditions and have their own characteristics so that they are able to mutually appreciate in diversity. This research is a qualitative research which is library research in which the research uses literature study and books as the main object. Mengawe is a custom and culture that unites people in the midst of diversity and is able to respect and support each other in the implementation process as a form of social beings that need each other, besides that Gawe also has family, social, togetherness, tolerance, and so on.